Novel mechanisms for the targeting of proteins into and across chloroplast membranes. (August 2000) - Woolhead, C.; Bolhuis, A.; Robinson, C.
Abstract : The assembly of the photosynthetic apparatus requires the translocation of numerous proteins from the cytosol, initially into the stroma and thereafter into or across the thylakoid membrane. Recent studies have shown that proteins are transported into this membrane by a variety of mechanisms, some of which are derived from a cyanobacterial-type ancestor, whereas others have evolved in response to the more complex transport pathway used by cytosolically synthesized chloroplast proteins. It is now apparent that some of the targeting pathways are used exclusively by hydrophobic thylakoid membrane proteins; here we review recent progress in our understanding of the biogenesis of this important class of protein.